Mechanical design and fabrication of Three-Wheel Electrical Vehicle (TWEV) - Noor Liyana, Mohd Zuki (2018)
A three-wheel electrical vehicle in which two front wheels are interconnected with a conventional vehicle frame such as motorcycle frame and also moving without using a petrol engine. This three-wheeled electric vehicle has an electric system to retribution the existing system which is a petrol system. To complete the electric system in this vehicle we used a suitable controller and a motor that can accommodate the load of vehicle. The connection between controller and motor we must used a suitable wiring system to avoid corruption while using this vehicle. The frame of three-wheeled electric vehicle was built follow the suitable design to stabilize the vehicle by using a tadpole design. By using this design the vehicle can achieved their balancing and prevent accident or broken down while moving. The characteristic of tadpole design is has two wheel in front one wheel at the back. To get a more stabilize in our chassis we observe it by using engineering software and used a simulation to test strength of our chassis.